Sinergi Perguruan Tinggi dan Pemerintah Daerah dalam Meningkatkan Kesadaran Hukum Perlindungan Perempuan dan Anak - Sri Wahyuni Laia; Dewi Ervina Suryani; Natasya Sabrina Kathlen Sihombing; Mesra Abadi Lase; Upi Indah Stevani Laoli (Jaanur Elbarik Indonesia, 2026)
Abstract: This community service activity aims to increase public legal awareness regarding the protection of women and children through legal counseling carried out synergistically between universities and the Population Control, Women's Empowerment and Child Protection Service of Gunungsitoli City. The methods used include interactive lectures, discussions, questions and answers, presentation of case studies, and evaluation of the level of understanding of participants before and after the activity. The counseling material includes the rights of women and children, forms of violence, reporting mechanisms, and legal protection efforts based on applicable laws and regulations. The results of the activity show an increase in participants' understanding of the legal rights of women and children, the ability to recognize forms of violence, and knowledge regarding reporting mechanisms and institutions authorized to provide protection.